Democracy and national identity in Thailand - Connors, Michael Kelly (RoutledgeCurzon research on Southeast Asia ;, 2003)
Explores the process of democratization in Thailand from the overthrow of the monarchist state in the 1930s to the present day and examines this development institutionally and ideologically through key issues.